Kontribusi Pendapatan Orang Tua, Kondisi Lingkungan Sekolah Dan Motivasi Terhadap Kedisiplinan Siswa Di SMP N 1 Pulokulon Kabupaten Grobogan Tahun Pelajaran 2016 / 2017 - Kuncorowati, Condro, Prof. Dr. Sutama,M.Pd, Dr. Suyatmini, M.Si (2017)
Objective 1) analyzes examine the contribution income of the parents, the condition of the learning environment and motivation to discipline students 2) analyzing test the revenue contribution of parents to discipline students. 3) analyze test conditions contribute to discipline the student learning environment. 4) analyzing test the contribution of motivation to discipline students. Results 1) There is a revenue contribution of older people, the condition of the learning environment and motivation together to discipline (F = 236.045, and p <0.05) so that is accepted. Effective contribution of independent variable income parents, environmental conditions and the motivation to learn collectively to discipline and the remaining 81.9% influenced by other variables that are not included. 2) The contribution of the parents discipline (t = 7.002 and p <0.05), is accepted. Effective contribution income of parents to discipline relative contribution of 25.0% to 30.5%. 3) There is a learning environment contributions discipline (t 02 = 5.381 and p <0.05), the is accepted. Effective contribution to the learning environment of discipline r 22.6% and the relative contribution of 27.6%. 4) The contribution of motivation (t = 8.164 and p <0.05) is accepted. Effective contribution to discipline motivation and the relative contribution of 34.3% to 41.9%.